Cu/Pd‐Catalyzed C‐2–H Arylation of Quinazolin‐4(3H)‐ones with (Hetero)aryl Halides. Issue 35 (6th November 2015) - Godeau, Julien; Harari, Marine; Laclef, Sylvain; Deau, Emmanuel; Fruit, Corinne; Besson, Thierry
Abstract: The regiospecific C‐2–H arylation of N‐3‐substituted quinazolin‐4(3 H )‐ones with a wide range of aryl or (hetero)aryl halides under microwave irradiation was studied. A ligand‐dependent palladium/copper bicatalytic system was developed and allowed direct cross‐coupling with a variety of (hetero)aryl halides. This useful and scalable procedure promotes the construction of C(sp 2 )–C(sp 2 ) bonds from arenes or (hetero)arenes and aryl or (hetero)aryl bromides and chlorides in a time‐efficient strategy. The extension of the reaction to various N‐3‐substituted quinazolin‐4(3 H )‐ones with iodobenzene as well as the scope and limitations of the method were also investigated. Abstract : The regiospecific C‐2–H arylation of N‐3‐substituted quinazolin‐4(3 H )‐ones with a wide range of aryl or (hetero)aryl halides under microwave irradiation is studied.